Analisa Sistem Informasi Administrasi Laboratorium pada Rumah Sakit Kanker Dharmais - Ardiansyah Ardiansyah; Ahmad Taufik (Jurnal Penelitian Teknologi Informasi dan Sains, 2024)
This study aims to conduct an in-depth analysis of the laboratory administration application system used at Dharmais Cancer Hospital. The research focuses on evaluating the system’s functionality, performance, and integration with other hospital systems to assess its effectiveness in supporting laboratory administrative operations. The research method employed a quantitative survey using a questionnaire that measured five key dimensions of service quality: Tangibles (physical appearance and facilities), Reliability, Responsiveness, Assurance, and Empathy (sensitivity to user needs) The findings indicate that the system’s functionality is categorized as "Good," with an average score of 76.8%, suggesting that the physical infrastructure effectively supports administrative processes. In terms of performance, the system scored well in responsiveness and reliability, achieving scores of 76% and 76.2%, respectively. However, improvements are needed to enhance system stability to ensure more consistent service delivery. The integration of the laboratory system with other hospital systems was also positively rated, with the highest score of 78.2% in the empathy dimension, indicating adequate flexibility in supporting various functions and coordination between departments.In conclusion, the laboratory administration application system at Dharmais Cancer Hospital is effective in supporting laboratory operations and services, though there is room for improvement, particularly in reliability and data integration aspects. The recommended improvements include enhancing system stability and strengthening integration capabilities to support better service efficiency.